Akuntabilitas Pelayanan Administrasi Kependudukan Di Kelurahan Purus Kota Padang - Melinda, Ivoni Yona; Asril, Asrinaldi; Valentina, Tengku Rika (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2019)
The accountability used as one of the benchmarks of bureaucratic performance in public service organization context. In 2016, Purus village chosen as the best village in Padang. But there are still found the complaints to Purus village such as long service and complicated. The purpose of this thesis is to analyze and explain the accountability of public service in Purus village at 2016/2017. This thesis use qualitative method and descriptive. The technique of data collection are interview and documentation. In the selection of research informant, the researcher used purposive sampling technique. The result of this thesis show that the accountability of public service in Purus village already accountable, but not maximal, Its because two of three indicators to see the accountability of public service that used maximal in Purus village, is For performance service indicator in Purus village, and accountability of product service indicator. For cost service, its still found take and give tradition that is not appropriate with the rules.